Performance of Bt maize event MON810 in controlling maize stem borers Chilo partellus and Busseola fusca in Uganda - Otim, Michael; Alibu, Simon; Asea, Godfrey; Abalo, Grace; Pyton Sserumaga, Julius; Adumo, Stella; Alupo, Jane; Ochen, Stephen; Tefera, Tadele; Bruce, Anani Yaovi; Beyene, Yoseph; Meisel, Barbara; et al. (Elsevier, 2022)
Stem borers are major insect pests of maize in Uganda. A study was conducted in 2014–2016 to assess the performance of Bt hybrids expressing Cry1Ab (event MON810) against the two major stem borer species in Uganda – the African stem borer (Busseola fusca) and the spotted stem borer (Chilo partellus) – under artificial infestation. The study comprised 14 non-commercialized hybrids, including seven pairs of Bt and non-Bt hybrids (isolines), three non-Bt commercial hybrids and a conventional stem borer resistant check. All stem borer damage parameters (leaf damage, number of internodes tunneled and tunnel length) were generally significantly lower in Bt hybrids than in their isolines, the conventionally resistant hybrid, and local commercial hybrids. Mean yields were significantly higher by 29.4–80.5% in the Bt hybrids than in the other three categories of non-Bt hybrids. This study demonstrated that Bt maize expressing Cry1Ab protects against leaf damage and can limit entry of stem borers into the stems of maize plants, resulting in higher yield than in the non-transgenic hybrids. Thus, Bt maize has potential to contribute to the overall management package of stem borers in Uganda.